Faktor-Faktor Yang Berhubungan Dengan Kejadian Stunting Pada Balita 6-59 Bulan Di Wilayah Kerja Puskesmas Mooat Kabupaten Bolaang Mongondow Timur Sulawesi Utara - Wida , Irne; Zainar; Devinsia , Debora (Politeknik Kesehatan TNI AU Ciumbuleuit Bandung, 2025)
Background : Stunting is described as a growth disorder that causes the failure to reach growth potential, leading to suboptimal health and nutrition status. This nutritional condition, known as stunting, is defined as stunted growth (short stature) based on anthropometric measurements, specifically Length for Age (L/A) or Height for Age (H/A). Objective : To determine the factors associated with the occurrence of stunting in children aged 6-59 months in the Mooat Health Center area. Method : This study uses a case-control design. The sampling technique used is total sampling, with 34 stunted children as cases and 34 non-stunted children as controls, resulting in a 1:1 case-to-control ratio. Results : The chi-square test for Maternal Knowledge obtained a p-value of 0.003, indicating that Maternal Knowledge is a factor associated with stunting, with an Odds Ratio (OR) of 0.223 (95% CI 0.080-0.624). This means that children with mothers who have low knowledge are 0.223 times less likely to experience stunting. The chi-square test for Exclusive Breastfeeding obtained a p-value of 0.001, indicating that Exclusive Breastfeeding is a factor associated with stunting, with an OR of 0.190 (95% CI 0.067-0.545). This means that children who are not exclusively breastfed are 0.190 times more likely to experience stunting. The chi-square test for Birth Weight obtained a p-value of 0.000, indicating that Birth Weight is a factor associated with stunting. The OR value of 53.308 (95% CI 6.487-438.049) means that children with a birth weight of <2500 grams are 53.308 times more likely to experience stunting Conclusion: The factors of Maternal Knowledge with a p-value of 0.003, Exclusive Breastfeeding with a p-value of 0.001, and Birth Weight with a p-value of 0.000, conclude that these factors have a significant relationship with the occurrence of stunting in the Mooat Health Center working area.